Відтворення соціокультурної складової у перекладі (на прикладі твору Д. Брауна «Янголи і демони») - Семигінівська, Тетяна Григорівна; Смірнова, Тетяна Володимирівна; Semyhinivska T. H., Smirnova T. V. (Східноєвропейський національний університет імені Лесі Українки, 2013)
Досліджено особливості відтворення соціокультурного компонента в англійській мові засобами української. Попри те, що проблематика соціокультурних цінностей вивчалася багатьма науками (соціологією, філософією, культурою, психологією та ін.), багато питань щодо передачі соціокультурних аспектів засобами мови, якою перекладають, залишаються не розглянутими. Чільне місце з-поміж них посідають реалії, способам перекладу яких і присвячене наше дослідження. The article is dedicated to the peculiarities of the socio-cultural component in the English language by means of the Ukrainian one. Regardless of the fact, that the issue of socio-cultural values was considered by many disciplines (such as: sociology, philosophy, culture studies, psychology etc.) many problems as for rendering socio-cultural aspects by means of the target language are still not solved. The research under consideration is dedicated to the means of translating realia being a socio-cultural constituent. Realia as language units express culture-specific peculiarities and do not represent any difficulties in translation if they can be rendered by means of transcription or transliteration. To adequately render realia which do not have correspondences in the target language the translator should substitute them by neutral words, use surrounding context or fill up lacuna.
Reproduction of the Sociocultural Constituent in Translation (Based on «Angels and Demons» by D. Brown)
Keywords: соціокультурний аспект; socio-cultural aspect; соціокультурні цінності; socio-cultural values; реалії; realia